PORTOFOLIO OPTIMAL BERDASARKAN MODEL INDEKS TUNGGAL PADA SAHAM BISNIS-27 DI BURSA EFEK INDONESIA - Ulpa Anggraini, Desi; Choiriyah, Choiriyah; Aldama, Kurnia (Jurnal Ilmu Manajemen, 2016)
This aimed of study was to analyze the form optimal portfolio BISNIS-27 Indonesia Stock Exchange in period May 2011 to November 2015. This study is used Single Index Model. The data used in this study was daily adjusted close price on period May 2011-November 2015. The sample was taken by using purposive sampling, which was always grouped BISNIS-27 Index.The result of the study showed that the use Single Index Model on 13 companies in BISNIS-27 exchange stock group for 10 period (May 2011-November 2015) found that there was 6 stock with each fund INCO (55.2797%), BSDE (37.171%), TLKM (4.947%), ADRO (0.17325%), KLBF (0.739%), and BBRI (0.1308%). Based on the calculation, the investor will receive the return portfolio about 0.524% with the risk of the portfolio about 0.0264%.